MG-132 Next-generation sequencing in the neonatal intensive care unit: Pilot data from 12 newborns. (4th December 2015) - Daoud, Hussein; Luco, Stephanie M; Li, Rui; Armour, Christine; Carson, Nancy; Jarinova, Olga; Nikkel, Sarah; Richer, Julie; Majewski, Jacek; Boycott, Kym; Dyment, David
Abstract : Background: Rare disease can present in the first days and weeks of life and is associated with significant morbidity and mortality. The genetic and clinical heterogeneity of these conditions can pose a significant challenge for diagnosis. Objective: To evaluate the diagnostic utility of the Illumina TruSightTM One panel, we performed Next-generation sequencing (NGS) for a series of 20 newborns presenting with features suggestive of a Mendelian disease in the Neonatal Intensive Care Unit (NICU). Design/methods: Twenty patients were recruited from the NICU at the Children's Hospital of Eastern Ontario. Inclusion criteria required a complex medical presentation (congenital anomalies, abnormalities in growth and/or neurological features). We used a family-based trio approach. Target enrichment was performed with the Illumina TruSightTM One Sequencing Panel kit. This panel targets 4, 813 genes that are deemed clinically-relevant and referred to as the "clinome". Sequencing was performed on the Illumina MiSeq. NextGene software (v2.3.4.4) was used for analyses. Time from sample acquisition to data analysis was possible in 7 working days. Results/conclusion: To date, 13 trios were sequenced and analysed. A molecular diagnosis was made in 5 of 13 patients, comparable to the rate obtained by whole-exome sequencing from the literature. Positive cases included bi-allelic mutations in WDR19 and ACE, an X-linked mutation in MTM1, homozygous mutations in FTO, and a de novo mutation in SCN1A. Clinome sequencing has the potential to improve our ability to efficiently diagnose rare diseases in the NICU by providing a cost-effective tool to evaluate the clinically relevant portion of the genome in a week's time.